DAILY RAINFALL DISAGGREGATION: AN ANALYSIS FOR THE RIO GRANDE DO SUL STATE - Leitzke Caldeira, Tamara; Beskow, Samuel; Mello, Carlos Rogério de; Martins Vargas, Marcelle; Soares Guedes, Hugo Alexandre; Coll Faria, Lessandro (Scientia Agraria, 2016)
ABSTRACT: Watershed hydrology is greatly dependent on the analysis of intense rainfall, especially when management and conservation of soil and water, flood management and hydraulic designs are necessary. The intense rainfall modeling should preferably use pluviographic data; however, this type of record is more infrequent than daily rainfall. As a result, methodologies of daily rainfall disaggregation have been commonly adopted to adjust intensity-duration-frequency (IDF) curves. This study had as main objective to evaluate the influence of three sets of disaggregation constants on the estimation of rainfall intensities using IDF curves adjusted from daily rainfall series in the state of Rio Grande do Sul. Based on the substantial variation of the coefficients for the 15 municipalities evaluated in this study, it can be stated that the disaggregation constants exerted influence on the adjustment of the IDF curves. Considering the statistical measure applied in this study, the best adjustment was obtained for the disaggregation constants proposed by CETESB. In order to make it available more realistic results in Rio Grande do Sul State for the decision-making in the scope of water resources, it is advisable to: i) use longer and more recent pluviographic data series for the state; ii) evaluate multiparameter probability distributions; and iii) determine regional disaggregation constants.